Practical analysis of IEEE 802.11b/g cards in multirate ad hoc mode - Katarzyna Kosek; Szymon Szott; Marek Natkaniec; Andrzej R. Pach (Journal of Telecommunications and Information Technology, 2023)
In multirate ad hoc networks, mobile stations usually adapt their transmission rates to the channel conditions. This paper investigates the behavior of IEEE 802.11b/g cards in a multirate ad hoc environment. The theoretical upper bound estimation of the throughput in multirate ad hoc networks is derived. The measurement scenarios and obtained results are presented. For result validation the theoretical and experimental values are compared. The achieved results, presented in the form of figures, show that cards manufactured by independent vendors perform differently. Therefore, choosing the optimum configuration, according to the user’s requirements, is possible